PWE-008 Placide: Probiotics in the Prevention of Antibiotic Associated Diarrhoea (AAD) and Clostridium Difficile Associated Diarrhoea (CDD) in Elderly Patients Admitted to Hospital – Results of a Large Multi-Centre RCT in the UK. (4th June 2013) - Allen, S; Wareham, K; Wang, D; Bradley, C; Sewell, B; Hutchings, H; Harris, W; Dhar, A; Brown, H; Foden, A; Gravenor, M; Plummer, S; et al.
Abstract : Introduction: Antibiotic associated diarrhoea (AAD) and Clostridium difficile associated diarrhoea (CDD) occur in 5–39% of pts exposed to antibiotics. Despite previous papers proposing a beneficial role of probiotics, there has been no large randomised controlled trial evaluating their preventative effect. Methods: This large RCT funded by the HTA was aimed at finding the efficacy and cost-effectiveness of a high dose, multi-strain probiotic for prevention of AAD and CDD in older people admitted to hospital. Pts aged > 65yrs, exposed to one or more oral/parenteral antibiotics without pre-existing diarrhoea, recent CDD or risk of probiotic adverse effects were eligible. Of 17, 420 patients screened, 2, 981(17.1%)were recruited and allocated sequentially by a computer-generated random allocation sequence stratified by centre. 1, 493(50.1%)were allocated to probiotic and 1, 488(49.9%)to placebo arm. Two strains of lactobacilli and two strains of bifidobacteria with a total of 6x1010 organisms/day were taken as a daily single capsule for 21 days. The placebo was inert maltodextrin powder. Occurrence of AAD or CDD within 12 weeks of recruitment was assessed by research nurses, blinded to arm allocation. Results: ITT analysis included 2, 941(98.7%)participants. Potential risk factors for antibiotic-associated diarrhoea at baseline were similar in both arms. The frequency of AAD was similar in the probiotic (159/1470, 10.8%)and placebo arms (153/1471, 10.4%), RR: 1.04; 95%CI0.84–1.28; P = 0.72.CDD was an uncommon cause of AAD and occurred in 12/1470(0.8%)participants in the probiotic and 17/1471(1.2%)in the placebo arm (RR 0.71; 95%CI0.34–1.47; P = 0.35).Adverse events and other outcomes were similar in both arms. Total health care costs per patient did not differ significantly between probiotics (£8020.11; 95%CI£7622.31-£8417.90) and placebo (£8011.37; 95%CI£7600.53-£8422.22).The incremental cost-effectiveness ratio of £45, 636/QALY was robust to changes in key parameters. Conclusion: This study found no evidence that probiotic administration was effective in the elderly in preventing AAD, although there was a trend towards reduced CDD in the probiotic arm. Disclosure of Interest: S. Allen: None Declared, K. Wareham: None Declared, D. Wang: None Declared, C. Bradley: None Declared, B. Sewell: None Declared, H. Hutchings: None Declared, W. Harris: None Declared, A. Dhar Grant/Research Support from: NIHR Grant Holder, Speaker bureau with: Shire Pharmaceuticals, Warner Chilcott UK, H. Brown: None Declared, A. Foden: None Declared, M. Gravenor: None Declared, S. Plummer Employee of: Research Director of Obsidian Research Limited and Director of Cultech Limited, D. Mack: None Declared, C. Phillips: None Declared